On Duffing equation with random perturbations - Ambrazevičius, A.; Ivanauskas, F.; Pragarauskas, H. (Nonlinear Analysis: Modelling and Control, 2010)
We consider a family of particles with different initial states and/or velocities whose dynamics is described by a modified Duffing equation with random perturbations. Sufficient conditions ensuring almost identical sample paths of the particles after a long time are given.